Children's cognitive recovery after day‐case general anesthesia: a randomized trial of propofol or isoflurane for dental procedures. Issue 2 (11th December 2013) - Millar, Keith; Bowman, Adrian W.; Burns, Deirdre; McLaughlin, Paul; Moores, Tony; Morton, Neil S.; Musiello, Toni; Wallace, Ewan; Wray, Alyson; Welbury, Richard R.; Anderson, Brian
Summary Background Postoperative cognitive dysfunction (POCD) is well established in adults but has been underinvestigated in children. As day‐case procedures are increasingly common, it is important to establish whether children suffer significant POCD. Pediatric POCD has been associated with several intravenous and inhalation anesthetics, but isoflurane has not been studied. As evidence indicates superior recovery after propofol, the study compared POCD after propofol or isoflurane anesthesia. Objectives To compare the effects of propofol versus isoflurane upon children's POCD. Methods Fifty‐eight children aged 5–14 years were randomized to propofol (total intravenous anesthesia) or isoflurane for day‐case dental procedures. Reaction time (RT), verbal and visual memory, psychomotor coordination, and attention were assessed preoperatively, prior to discharge and at 24 h. Results Reaction time and psychomotor control were impaired postoperatively in both groups but recovered at 24 h. Delayed verbal recall was significantly impaired only after propofol. Both groups had significant impairment of visual memory postoperatively and at 24 h, and of recognition memory postoperatively only. Conclusions Propofol and isoflurane exert similar adverse effects on RT, psychomotor coordination, and visual memory. Selective impairment of verbal recall by propofol is consistent with adult evidence of the drug's effect on retrieval. The enduring postoperative impairment of memory has implications for instructions to parents and caregivers for the safety and well‐being of children in the 24 h after day‐case anesthesia with propofol and isoflurane.